The Experience of Post-War Reconstruction: The Case of Built Heritage in Bosnia - Kudumovic, Lana (Emerald Publishing, 2020)
Purpose – The purpose of this paper is to discuss the challenges and justification of the reconstruction of built heritage in Bosnia. This paper also debates the effect of setting up a close relationship between reconstruction and reconciliation, suggesting that the reconstruction of the built environment in the period of post-war recovery provided a foundation for reconciliation. Design/methodology/approach – Throughout history, in the face of various disasters, world encountered the challenge of reconstruction. In the past decade of the 20th century, just such a challenge was the war in Bosnia. After the war, reconstruction and reconciliation took place, with a focus on reestablishing a normal way of life, the return of displaced people, and the reconnection of broken bonds, as well as the rehabilitation of heritage assets. Findings – This paper elaborates on how reconstructions were guided by the aims of reconciliation and its justifications. Regarding the technical aspects of these reconstruction projects, an overview comprising several case studies is presented to help elucidate two levels of physical intervention. The first of these levels concerns the reconstruction of single structures and the second concerns the reconstruction of historic centers. War memorials are considered to be a third level of intervention. Originality/value – The selected cases presented here confirm the existence of the relationship between post-war reconstruction and reconciliation. This paper also assesses the efficiency of the reconstruction of Bosnia’s built heritage in terms of authenticity and overall post-war recovery.
Keywords: Post-War Reconstruction; Recovery; Built Heritage; Rehabilitation; Reconciliation